Coexistence of Negative and Positive Photoconductivity in Few‐Layer PtSe2 Field‐Effect Transistors. (3rd August 2021) - Grillo, Alessandro; Faella, Enver; Pelella, Aniello; Giubileo, Filippo; Ansari, Lida; Gity, Farzan; Hurley, Paul K.; McEvoy, Niall; Di Bartolomeo, Antonio
Abstract: Platinum diselenide (PtSe2 ) field‐effect transistors with ultrathin channel regions exhibit p‐type electrical conductivity that is sensitive to temperature and environmental pressure. Exposure to a supercontinuum white light source reveals that positive and negative photoconductivity coexists in the same device. The dominance of one type of photoconductivity over the other is controlled by environmental pressure. Indeed, positive photoconductivity observed in high vacuum converts to negative photoconductivity when the pressure is raised. Density functional theory calculations confirm that physisorbed oxygen molecules on the PtSe2 surface act as acceptors. The desorption of oxygen molecules from the surface, caused by light irradiation, leads to decreased carrier concentration in the channel conductivity. The understanding of the charge transfer occurring between the physisorbed oxygen molecules and the PtSe2 film provides an effective route for modulating the density of carriers and the optical properties of the material. Abstract : The channel current measured in the PtSe2 field‐effect transistor under switching light shows positive photoconductivity at low pressure that converts into negative photoconductivity at atmospheric pressure. Experimental observations and density functional theory calculations demonstrate that such behavior is caused by light‐induced oxygen desorption.